2018
DOI: 10.18052/www.scipress.com/ilshs.82.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Farmers' Vulnerability to Climate Change in Niger State, Nigeria

Abstract: Abstract. This research evaluates the farmers' vulnerability to climate change in Niger State. Strategies for reducing the effect of climate change have regularly been made without experimental foundations and adequate information on farmers' vulnerability to climate change in the study area. Thus, integrated farmers' vulnerability assessment approach was employed by classifying socioeconomic and biophysical indicators of vulnerability into adaptive capacity, sensitivity and exposure to determine the farmers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Irrigation projects which would have served to mitigate these problems were also affected by water shortages as most of the dams dried up during droughts, thus, exacerbates the impact of droughts on the environment and human comfort. Abaje et al (2013) state that during drought periods, the land is under increased stress from both human beings and livestock, through unsustainable agricultural practices, leading to increasing desertification (Oyekale 2009;Eze et al 2018). Mortimore et al (2009) have shown that overgrazing becomes destructive during drought, when large areas that would normally have been available for grazing dry up, animals are forced to feed on any available edible vegetation they could find.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Irrigation projects which would have served to mitigate these problems were also affected by water shortages as most of the dams dried up during droughts, thus, exacerbates the impact of droughts on the environment and human comfort. Abaje et al (2013) state that during drought periods, the land is under increased stress from both human beings and livestock, through unsustainable agricultural practices, leading to increasing desertification (Oyekale 2009;Eze et al 2018). Mortimore et al (2009) have shown that overgrazing becomes destructive during drought, when large areas that would normally have been available for grazing dry up, animals are forced to feed on any available edible vegetation they could find.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, about 65% of the total respondents depends primarily on farming, thus increasing drought occurrences affects household revenue generation and food availability in the study area. Eze et al (2018) argue that households whose livelihood depends on farming suffer losses during drought because the crop yield and livestock production are reduced and also, the weight and strength of cattle for the purpose of draught power is drastically reduced. Moreover, the frequent incidences of droughts resulted to the lowering of water table and sustenance of few rivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abaje et al [38] GS CVI Adeoti et al [39] GS CVI Adewuyi et al [40] TR, GS CVI Ajibola [18] All LnCLAH Atedhor [36] SdS U Awolala and Ajibefun [41] TR, GS CVI Awoyemi and Olajide [42] All CVI Ayanlade and Ojebisi [43] GS D, FS Aye and Ater [44] All CY Building Nigeria's Response to Climate Change (BNRCC) [6] ShS, GS, TR, MF V Cervigni et al [45] All CY, LTHI, LGPP Chikezie et al [46] TR CVI Chukwuemeka et al [47] TR CVI Eze et al [48] GS CVI Madu [37] All CVI Madu [49] All CVI Manu et al [50] GS, SdS CVI Medugu and Majid [51] U CVI Ojo et al [52] GS CY Umar et al [35] SdS, ShS The theoretical backgrounds typically provide a guide for the conceptual frameworks used to operationalize vulnerability assessments [12]. Table 3 further shows that studies applied different methods to construct a composite vulnerability index.…”
Section: Measure Theory Subjective Socioeconomic Biophysical Integratmentioning
confidence: 99%